KAJIAN FINANSIAL ISOLASI CITRONELLAL DAN RHODINOL PADA INDUSTRI bERBASIS SENYAWA TURUNAN MINYAK SEREH WANGI - Retno Sri Endah Lestari; Djumali Mangunwidjaja; Ani Suryani; Anas Miftah Fauzi; Meika Syahbana Rusli (AGROINTEK, 2012)
Isolation components of Citronellal and  Rhodinol in citronella oil can be applied to the industry to increase the added value and develop intermediate industries of citronella oil. To determine the feasibility of implementation, financial analysis is required to process such isolation. Feasibility of investment in new industrial establishment or development of NPV seen citronella oil  industry, BEP, PBP, Net B / C and IRR can describe whether the project is still attractive to be realized. On the establishment of new industries, the NPV value of Rp11, 844,269,430.12, an IRR of 47%. The payback period (PBP) is achieved over a period of 2.79 years. Net value of B / C is 2.75 and the production break-even point (BEP) is obtained on the sale value of Rp. 5,217,742,676.09. While the development of citronella oil industry, the NPV of the industrial development of Rp 12,348,032,363.16. IRR value for industrial development with 600 kg Input / process is 89%. The payback period (PBP) industrial development achieved during the period of 4.41 years. Net value of B / C obtained from the establishment Factory is 6.30. Production break-even point (BEP) is obtained on the sale value of Rp 20,912,029,225.35. This suggests that the establishment of new industries and the development of scented citronella oil industry that already exist, worthy to be realized